KEHIDUPAN BERAGAMA DI INDONESIA DALAM PERSPEKTIF HERMENEUTIKA KRITIS JÜRGEN HABERMAS - Babo, Alkuinus; Vinsensius Fererius Ratman; Mathias Jebaru Adon (Sanjiwani: Jurnal Filsafat, 2026)
This study focuses on examining Jurgen Habermas's concept of critical hermeneutics and its contribution to the understanding of religious life in Indonesia. Religious life today tends to be under attack by various ideologies and interests that have the potential to damage social relations between believers. Based on this background, this study asks the following questions: (1) How does Jurgen Habermas's concept of critical hermeneutics reveal the ideological interests behind authority and tradition? And (2) How relevant are these concepts to building an inclusive religious ethic in Indonesia? This research uses a literature review method with a critical hermeneutic approach. Analysis is conducted through critical-reflective interpretation of texts, exploring ideological dimensions, power relations, and communication distortions in religious practices. This approach is also enriched with discourse analysis to uncover hidden interests that hinder religious understanding. The results show that Jurgen Habermas's critical hermeneutics offers a relevant framework for developing a dialogical, rational, and inclusive religious ethic. This approach encourages communication free from domination, manipulation, and repression, while fostering critical awareness in the face of plurality. Thus, critical hermeneutics contributes to building a more harmonious, just, and tolerant religious life amidst the diversity of Indonesian society.